Characteristics of wetting behavior under unloading in natural granite residual soil - Song Yin; Jianing Huang; Xinming Li; Yuzhou Sun; Yuru Li; Xianwei Zhang (Scientific Reports)
Abstract Excavation of foundation pits induces stress release in the soil, leading to deformation driven by the redistribution of internal stresses and particle adjustment. Rainfall infiltration further increases soil water content, weakening particle bonding through the dissolution of cementing agents, and inducing additional wetting deformation. However, there has only been limited experimental research examining the deformation behavior of soil under the coupled effects of unloading and wetting, especially in water-rich excavation conditions, where these factors interact dynamically. This study systematically investigates the coupled effects of unloading and wetting on the deformation behavior of natural granite residual soil (GRS) through triaxial tests. The results reveal that the interaction between unloading and wetting amplifies soil deformation, with significant non-linear dependencies on confining pressure and saturation levels. The stress–strain curves of natural GRS under unloading path exhibit strain-hardening behavior, and the vertical wetting deformation decreases with increasing saturation. Furthermore, the study identifies pronounced anisotropic wetting deformation, with tensile wetting deformation significantly exceeding compressive wetting deformation under equivalent stress states. This anisotropy diminishes with increasing confining pressure, highlighting the stress-dependency of wetting deformation behavior. The hyperbolic model shows a larger wetting deformation than the linear model, underscoring its practical significance in designing safer excavation strategies under coupled unloading and wetting conditions. These findings provide a foundation for improving deformation prediction and risk management in geotechnical engineering.